2018
DOI: 10.1038/s41598-018-31039-8
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 degradation by combined TRAIL and valproic acid treatment induces apoptotic cell death of TRAIL-resistant head and neck cancer cells

Abstract: Although TRAIL can directly induce cell death in some cancer cells, it appears that TRAIL resistance exists in many cancers. This study focuses on anti-cancer drugs for TRAIL-resistant head and neck cancer (HNC) to provide further progress toward effective cancer therapy. Results indicate in TRAIL-resistant HNC cells, that combined TRAIL and VPA treatment greatly reduced cell viability and therefore induced cell death, relative to treatment with TRAIL or VPA alone. A caspase-dependent signaling pathway was dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The human HDAC4 gene, located on chromosome 2q37.3, has been found to be involved in initiation and development of various cancers, and functions as an oncogene in many cancers [32][33][34][35][36]. A previous study confirmed HDAC4 as a target of miR-29b-3p in MM cells [25].…”
Section: Discussionmentioning
confidence: 94%
“…The human HDAC4 gene, located on chromosome 2q37.3, has been found to be involved in initiation and development of various cancers, and functions as an oncogene in many cancers [32][33][34][35][36]. A previous study confirmed HDAC4 as a target of miR-29b-3p in MM cells [25].…”
Section: Discussionmentioning
confidence: 94%
“…HDACs also deacetylate non-histone cellular substrates and influence a variety of biological processes that govern cancer initiation and progression [ 42 ]. HDAC4 is upregulated in head and neck cancer tissues [ 43 ]. HDAC4 is targeted by HDAC inhibitors ( Figure 2 b).…”
Section: Discussionmentioning
confidence: 99%
“…The survival and growth of multiple myeloma is regulated by the HDAC4-RelB-p52 complex, and the disruption of the latter blocks the growth of these cells [ 46 ]. Moreover, HDAC4 degradation by certain chemotherapeutic agents results in the apoptosis of head-and-neck cancer cells that are resistant to TRAIL, while miR-22-driven HDAC4 repression helped to resensitize fulvestrant-resistant breast cancer cells [ 47 , 48 ]. Likewise, eptoposide resistance in human A549 lung cancer cells was conferred by STAT1-HDAC4 upregulation, and HDAC4 inhibition has been reported to induce apoptosis in non-small cell lung cancer PC-9 cells [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%